Historical snow measurements in the central and southern Apennine Mountains: climatology, variability, and trend - V. Capozzi; F. Serrapica; A. Rocco; C. Annella; C. Annella; G. Budillon (The Cryosphere, 2025)
This work presents an analysis of historical snow precipitation data collected in the period 1951–2001 in central and southern Apennines (Italy), an area scarcely investigated so far. To pursue this aim, we used the monthly observations of the snow cover duration, number of days with snowfall and total height of new snow collected at 129 stations located between 288 and 1750 m above sea level. Such data have been manually digitised from the Hydrological Yearbooks of the Italian National Hydrological and Mareographic Service. The available dataset has been primarily analysed to build a reference climatology (related to the 1971–2000 period) for the considered Apennine region. More specifically, using a methodology based on principal component analysis and k-means clustering, we have identified different modes of spatial variability, mainly depending on the elevation, which reflect different climatic zones. Subsequently, focusing on the number of days with snowfall and snow cover duration on the ground, we have carried out a linear trend analysis, employing the Theil–Sen estimator and the Mann–Kendall test. An overall negative tendency has been found for both variables. For clusters including only stations above 1000 m above the sea level, a significant (at 90 % or 95 % confidence levels) decreasing trend has been found in the winter season (i.e. from December to February), with −3.2 [−6.0 to 0.0] d per 10 years for snow cover duration and −1.6 [−2.5 to −0.6] d per 10 years for number of days with snowfall. Moreover, in all considered seasons, a clear and direct relationship between the trend magnitude and elevation has emerged. In addition, using a cross-wavelet analysis, we found a close in-phase linkage on a decadal timescale between the investigated snow indicators and the Eastern Mediterranean teleconnection Pattern. For both snow cover duration and number of days with snowfall, such connection appears to be more relevant in the full (i.e. from November to April) and in the late (i.e. from February to April) seasons.